Vocal Self Assessment Questionnaire: Epidemological Control Tool of the Ocupational Dysphonic Syndrome in Professors - de Almeida, Sandra Irene Cubas; Pontes, Paulo; Bussacos, Marco Antonio; Neves, Luciano; Zambon, Fabiana (Arquivos Internacionais de Otorrinolaringologia, 2010)
Introduction: The dysphonic syndrome is an occupational disease of high prevalence in the professor population.Objective: In order to broach preventively the vocal aggression, it was tried to standardize a self assessment questionnaire to professors of all educational level, including beyond the clinical symptoms also the factors of the work organization.Method: It was performed a study of transversal cut in 328 professors of 4 educational institutions of the northern of São Paulo, which it was applied a self assessment questionnaire elaborated by TRipartite Commission of Standardization for Professional Voice.Results: It was determined the prevalence of clinical symptoms that compound the dysphonic syndrome, as well as it was delineate the work organization and the quality of life of this population.Conclusion: The questionnaire applied was showed itself satisfactory en the description and elaboration of parameters with the aim of to implement preventive programs to populations exposed to professional overload of the voice use. Case study.
Keywords: dysphonia; occupational medicine; occupational risks; worker health; research